Pancreatic Metastasis from Renal Cell Carcinoma Several Years after Nephrectomy: Two Case Reports and Literature Review - Ghattas, Souad; Bitar, Jad El; Maalouf, Hani; Bulbul, Tarek; Tabbikha, Omar; Dib, Wissam; Asmar, Antoine El; Rahban, Hind; Rassi, Ziad El (The Surgery Journal, 2025)
Metastases of renal cell carcinoma (RCC) to the pancreas are infrequent, comprising only 1 to 4% of pancreatic malignancies. These cases are distinguished by a prolonged period of being free from the disease following the initial surgery. We present here two rare cases of isolated pancreatic metastases from RCC, occurring 7 to 8 years after nephrectomy. The patients were asymptomatic; the masses were discovered incidentally during their routine annual health checkup. Surgical resection of these oligometastases was the appealing choice for managing these cases, potentially complemented by systemic treatment. The late onset of metastasis from RCC in solid organs should always be considered when dealing with patients with a history of RCC. Additionally, the follow-up following nephrectomy for RCC should be extended over 10 years.
Keywords: renal cell carcinoma; pancreatic metastasis; pancreatectomy; metastasectomy; late onset